Influence of Instrumentation Kinematics on Root Canal System Preparation: a Sytematics Review of Studies by Micro-computed Tomography - Augusto Julio Munoz; Jefferson José de Carvalho Marion; Amanda Falcão; Daniel Rodrigo Herrera (Portal de Periódicos da Marinha do Brasil, 2022)
The objective of this study was to conduct a systematic review focused on studies that used micro-computed tomography (micro-CT) analysis to evaluate untouched canal areas after root canal preparation with continuous rotary and reciprocating kinematics. Electronic search strategies were used in LILACS, PubMed (MedLine), Science Direct, Cochrane, Scopus and Web of Science databases. An additional search for gray literature was performed on Google Scholar, OpenGrey and ProQuest. In addition, manual searches were performed on the reference list of included articles. It covered studies in English, Portuguese and Spanish, without restriction regarding the publication time. The articles selected for inclusion in this review meet all the following criteria: in vitro studies that evaluated, with the use of micro-CT, the percentage of untouched areas after root canal preparation comparing rotary and reciprocating kinematics. A total of 11 studies were selected for qualitative and quantitative analysis. One study showed that the Reciproc system has a smaller percentage of untouched channel walls in lower incisors when compared to BioRace system. Another study showed no significant differences between reciprocating systems Reciproc and WaveOne with BioRace in mesial root canals of lower molars. Similarly, they did not observe any difference between ProTaper Next and ProTaper Universal with WaveOne. A single study showed differences between XP-Endo Shaper system (rotary) compared with WaveOne Gold. The studies evaluated in the present review showed by micro-CT that none of the instrumentation systems, regardless of the kinematics used or NiTi heat treatment, was able to completely touch the root canal walls.